Optimalisasi Peran PKK Dalam Meningkatkan Nilai Ekonomi Komoditas Padi Di Tulang Bawang - Dwy April Cella Cella; Erlin Kurniati (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This study aims to analyze the optimization of the role of PKK (Family Welfare Empowerment) in increasing the economic value of rice commodities in Tulang Bawang Regency. Rice is a strategic commodity that supports the local economy; however, the majority of the harvest is still sold as unprocessed unhusked rice, which limits its added value and reduces potential income for farmers. This issue is caused by several factors, including limited access to appropriate processing technology, lack of training in product development, and insufficient market information. Through a qualitative descriptive approach based on literature review and secondary data, this research highlights the important role PKK can play in community empowerment, particularly among women farmers. PKK's involvement includes providing technical skills through training, encouraging entrepreneurship, and strengthening community-based social networks. Empowering PKK is not only essential for capacity building but also acts as a catalyst for local innovation and food processing efforts. The proposed strategies include implementing rice product processing training, enhancing product branding and promotion, establishing marketing networks, and integrating PKK programs into village development plans and local government agendas. The findings show that when PKK functions optimally, it has the potential to develop a household-based agricultural business ecosystem that improves local economic resilience, increases the added value of agricultural commodities, and strengthens food security in a sustainable and inclusive manner